GENDER DISPARITIES IN EMPLOYMENT IN NORTH LOMBOK REGENCY: A FEMINIST ECONOMIC ANALYSIS OF LABOR PARTICIPATION AND THE INFORMAL SECTOR - Ernaldo Fikrul Arifin; Muhammad Mahfuz; Dian Aulia Mutia Sari (Akademi Bisnis Lombok, 2025)
This study examines gender disparities in employment in North Lombok Regency through a feminist economic lens, analyzing labor force participation patterns and informal sector concentration. Using data from the 2024 National Labor Force Survey (Sakernas), this research reveals significant gender gaps in the labor market. The Labor Force Participation Rate (LFPR) shows a 22.06 percentage point gap, with males at 91.97% and females at 69.91%. The analysis demonstrates that 22.32% of working-age women are engaged in household duties compared to only 1.78% of men, reflecting the gendered division of reproductive labor. Furthermore, 82.28% of employed women work in the informal sector, predominantly as unpaid family workers (35.90%), while men have greater access to formal employment (32.17%) and wage positions (30.52%). This research employs a literature review methodology, integrating feminist economic theory to critique structural barriers that perpetuate gender inequality in employment. The findings indicate that patriarchal structures, unrecognized reproductive work, and occupational segregation systematically marginalize women in the labor market. The study concludes that addressing gender disparities requires policy interventions recognizing the economic value of care work, promoting women's access to formal employment, and transforming gender norms that confine women to domestic roles.